Hepatitis B virus infection in HIV-exposed infants in the Western Cape, South Africa. Issue 36 (26th August 2015) - Chotun, Nafiisah; Nel, Etienne; Cotton, Mark F.; Preiser, Wolfgang; Andersson, Monique I.
Abstract: Hepatitis B virus infection (HBV) is a significant public health problem in sub-Saharan Africa. Universal infant vaccination with the hepatitis B (HB) vaccine has been implemented within the South African Expanded Programme of Immunization since April 1995 with concomitant reduction in HBV infection in children. However, the first vaccine dose is only administered at six weeks of age. This delay may lead to a failure to reduce the risk of perinatal HBV transmission to infants born to HIV/HBV co-infected women, in whom HBV infection is often upregulated. The aim of this study was to determine the prevalence of HBV infection in babies born to HIV-infected mothers in the Western Cape, South Africa. HBV serological markers were tested in all infant serum samples and following HB viral load testing, sequencing and genotyping were also performed. Three of 1000 samples screened tested positive for HBsAg and HBV DNA. An additional infant tested positive for HBV DNA alone. All babies had received the HB vaccine at 6, 10 and 14 weeks. The prevalence of HBV infection was therefore 4/1000 (0.4%; 95% CI, 0.01–0.79%). Three of four infants and all four mothers were followed-up. Two infants were persistently positive for HBsAg with viral loads above 10 8 International Units per millilitre. All four maternal samples were positive for HBsAg and HBeAg and one was also positive for anti-HBe. Sequencing analysis of two mother–child HBV pairs showed 100% sequence identity. This study demonstrates HBV infection in HIV-exposed infants despite HB vaccination from 6 weeks of age. A more strategic approach is needed to prevent mother to child transmission of HBV, including screening of pregnant women, HBV-targeted antiviral therapy and HB birth dose vaccine.